Proceedings of the Conventions of the Province of Maryland Held at the City of Annapolis, in 1774, 1775, & 1776 Page 146-47, Image 146-47 (1836); 1776 Md. Laws 146 - (:unkn) unknown (General Publisher, 1776)
no muskets or rifles, except by the owner thereof on his removal to reside out of this province, or any gun barrels, gun locks, or bayonets, be carried out of his province, without the leave of the council of safety for the time being.]
--
Keywords: CARRY